Simple House Theory In Some Buginese Traditional Houses - Ja’faruddin Ja’faruddin; Hamda Hamda; Muhammad Darwis (Seminar Nasional LP2M UNM, 2022)
Abstract. Humans' natural mathematical abilities have propelled civilizations forward. Mathematics is an integral component of all cultural contexts, and the significance of all cultural contexts is influenced by the individual's interpretation within that culture. These interpretations have been demonstrated in cultural heritage, particularly traditional houses, which show evidence of intuitive mathematics ability. Tribes worldwide have built traditional houses in their distinct styles. The current study included data collection through documentation, observation, and interviews. Camera images, aerial camera images, and documentation techniques were used to observe several traditional buildings in Indonesia. We used projective geometry and simple house theory to analyze of the sample of traditional Houses. The result of the traditional house are (1) traditional house from NTB (west Nusa Tenggara) and Wajo ( Saoraja Latenri Bali) have building numbers and Projective coordinate , and chategorized as Simple house IV (2)Traditionla houses from Sidrap and Bone is categorized as simple house V with projective coordinate Keywords: House Theory, Projective Geometry, Traditional Houses, Building Numbers, Projective Coordinates